Make-Up Removers and Eye Surface - V. N. Trubilin; E. G. Poluninа; K. V. Chinenova; V. V. Kurenkov; S. G. Kapkova (Oftalʹmologiâ, 2021)
Purpose: to evaluate the influence on the state of the eye surface and the tear-producing system of decorative cosmetics and cosmetic products with different chemical bases for removing makeup.Patients and methods. The study included 45 (90 eyes) persons without clinical signs of an acute inflammatory process of the eye surface, they were prescribed the use of one of the Biore products: 15 people — makeup removal wipes, 15-micellar water, 15-makeup removal serum. The results of the objective (biomicroscopy, tests for lacrimal production) and subjective examinations are included in the questionnaires developed and standardized for this study (3 visits after the start of the use of cosmetics, 14, 30 days after the start of their use).Results. There were no significant differences (p > 0.5) between the groups that used makeup remover products on different bases — makeup remover serum, micellar water, makeup remover wipes — in all the patients included in the study. Patients with signs of a chronic inflammatory process on the eye surface and dry eye syndrome are less tolerant of makeup remover, which is manifested in a lower subjective assessment of these products after their use compared to patients without signs of an inflammatory process (p < 0.5). A correlation was determined at r = 0.3085, p = 0.0392 between the skin type and the Schirmer test parameters, exactly, the more oily the skin, the higher the Schirmer test parameters, it indicates a possible relationship between the skin type and the functional activity of the tear-forming glands, which indicates the need for further research in this area. The absence of a correlation (p > 0.5) between objective and subjective parameters that characterize the state of the eye surface and the tear-producing system, as well as the number of hours per day when decorative cosmetics are used, indicates that prolonged use of this type of exposure does not lead to the development of a pathological process on the eye surface.